Characterisation of rejuvenation of various modified asphalt binders based on simplified chromatographic techniques. Issue 12 (15th October 2022) - Guo, Meng; Liang, Meichen; Sreeram, Anand; Bhasin, Amit; Luo, Daisong
ABSTRACT: The use of reclaimed asphalt pavement (RAP) is believed to contribute significantly towards overall energy conservation and environmental protection efforts. However, the recycling of aged binder from RAP requires a fundamental understanding of the interaction mechanism between such rejuvenators with recycled and unmodified binders. This study quantitatively investigated the impact of such agents in combination with the aging-rejuvenation process and other binder modifiers (SBS, crumb rubber, and a high viscosity modifier) on the fractional composition, rheology, and colloidal structural stability of asphalt binders. Based on these results, a rejuvenation index ( RI ) was proposed to quantitatively evaluate the rejuvenation of aged asphalt binder. Aging increased the proportion of resins and asphaltenes of asphalt binders which resulted in the decrease of its rheological properties. After the addition of the rejuvenators, the complex modulus of all aged binders were reduced. Certain rejuvenators transformed up to 5 percentage points of asphaltenes into other fractions. The aromatic oil-based rejuvenator showed the best rejuvenation of unmodified asphalt binder, but the RI was only 0.33. Overall, the results implied that rejuvenation of asphalt binders is a complex topic and further studies should be conducted to correlate the rheological behaviour with rejuvenation mechanisms beyond chemical fractions.